Aneugenic potential of the anticancer drugs melphalan and chlorambucil. The involvement of apoptosis and chromosome segregation regulating proteins. Issue 7 (25th October 2011) - Efthimiou, Maria; Stephanou, Georgia; Demopoulos, Nikos A.; Nikolaropoulos, Sotiris S.
ABSTRACT: Previous findings showed that the anticancer drugs p‐N, N‐bis (2‐chloroethyl) amino‐l ‐phenylalanine (melphalan, MEL) and p‐N, N‐bis (2‐chloroethyl)aminophenylbutyric acid (chlorambucil, CAB) belonging to the nitrogen mustard group, in addition to their clastogenic activity, also exert aneugenic potential, nondisjunction and chromosome delay. Their aneugenic potential is mainly mediated through centrosome defects. To further investigate their aneugenicity we (a) studied whether apoptosis is a mechanism responsible for the elimination of damaged cells generated by MEL and CAB and (b) investigated if proteins that regulate chromosome segregation are involved in the modulation of their aneugenic potential. Apoptosis was studied by Annexin‐V/Propidium Iodide staining and fluorescence microscopy. The involvement of apoptosis on the exclusion of cells with genetic damage and centrosome disturbances was analyzed by DAPI staining and immunofluorescence of β ‐ and γ ‐tubulin in the presence of pan‐caspase inhibitor. The expressions of Aurora‐A, Aurora‐B, survivin and γ ‐tubulin were studied by western blot. We found that (a) apoptosis is not the mechanism of choice for selectively eliminating cells with supernumerary centrosomes, and (b) the proteins Aurora‐A, Aurora‐B and survivin are involved in the modulation of MEL and CAB aneugenicity. These findings are important for the understanding of the mechanism responsible for the aneugenic activity of the anticancer drugs melphalan and chlorambucil. Copyright © 2011 John Wiley & Sons, Ltd. Abstract : It is known that melphalan and chlorambucil exert aneugenic potential mediated through centrosome amplification. To further investigate their aneugenicity we: a) studied whether apoptosis is a mechanism for the elimination of damaged cells generated and b) investigated if chromosome segregation regulating proteins are involved in the modulation of their aneugenicity. We found that: a) apoptosis is not the mechanism of choice for selectively eliminating cells with supernumerary centrosomes and b) the proteins aurora‐A, aurora‐B and survivin are involved in the modulation of melphalan and chlorambucil aneugenicity.